Bay Leaf Decoction as A Complementary Therapy for Hypercholesterolemia: Evidence from a Community Health Center in East Java Province, Indonesia - Enny Puspita; Kusuma Wijaya Ridi Putra; Darsini; Asri Kusyani (Public Health of Indonesia, 2026)
Background: Hypercholesterolemia remains a major public health concern in Indonesia, contributing to increased cardiovascular risk. While statins are effective, their long-term use poses safety and accessibility challenges, prompting interest in complementary herbal therapies. Objective: This study aimed to evaluate the short-term effectiveness of a traditionally prepared bay leaf (Syzygium polyanthum) decoction, administered at 400 ml per day for 14 days, in reducing total cholesterol levels among individuals with hypercholesterolemia in a community health center setting. Methods: A quasi-experimental design was conducted at the Bangil Community Health Center, East Java, involving 100 Prolanis participants aged ≥35 years. The intervention group (n = 50) received 400 ml/day of bay leaf decoction for 14 days, while the control group (n = 50) received standard dietary counseling. Total cholesterol levels were measured before and after the intervention using a validated point-of-care device. Data were analyzed using the Wilcoxon Signed-Rank and Mann–Whitney U tests. Results: The intervention group showed a significant reduction in total cholesterol from 235.4 ± 18.2 mg/dL to 193.2 ± 16.7 mg/dL (p < 0.001), whereas the control group exhibited a non-significant decrease. The between-group difference was statistically significant (p < 0.001), with no adverse effects reported. Conclusion: Bay leaf decoction is a safe, effective, and culturally appropriate complementary therapy for managing hypercholesterolemia. Its integration into community-based healthcare may enhance cardiovascular disease prevention, particularly in resource-limited settings.